Informed Traders as Liquidity Providers: Anonymity, Liquidity and Price Formation - Rindi, Barbara (Review of Finance, 2008)
Abstract The tendency to introduce anonymity into financial markets apparently runs counter to the theory supporting transparency. This paper studies the impact of pre-trade transparency on liquidity in a market where risk-averse traders accommodate the liquidity demand of noise traders. When some risk-averse investors become informed, an adverse selection problem ensues for the others, making them reluctant to supply liquidity. Hence the disclosure of traders' identities improves liquidity by mitigating adverse selection. However, informed investors are effective liquidity suppliers, as their adverse selection and inventory costs are minimized. With endogenous information acquisition, transparency reduces the number of informed investors, thus decreasing liquidity. The type of information that traders hold and the effectiveness of insider trading regulation are crucial to distinguish between equilibria.